Performance of disposable Cu/CuSO4 reference electrode in reinforced concrete corrosion analysis - Muhammad Ihsan; Fonna, Syarizal; Huzni, Syifaul; Alva, Sagir; Ahmad Kamal Ariffin; Nurul islami (Penerbit Universiti Kebangsaan Malaysia, 2023)
The investigation of reference electrode performance for corrosion analysis has been widely conducted over the last decade. The need for a disposable and reliable reference electrode is a specific need for corrosion investigation. This research investigated the effectiveness of liquid-based and solid-state reference electrodes, which are disposable and provide reliable performance. The electrode was prepared with low-cost material preparation (disposable usage) within a Copper-Copper Sulphate (CCS) liquid-based and solid-state electrodes. The potential stability was already tested for dependability by measuring the Open Circuit Potential (OCP) on the rebar concrete specimen. The behaviour of solid-state reference and liquid-based reference electrodes in terms of polarization was studied in a corroded environment. Real-time potential data was also obtained for the corrosion rate investigation. The result shows the consistency performance of (OCP) value during corrosion measurement. The deviation of the maximum to a minimum potential value less than 0.02 V, verifies that the liquid-based copper (Cu) electrode and solid-state copper (Cu) electrodes are reliable, adaptable, and disposable for reinforced concrete corrosion measurement. In terms of corroded rebar potential measurement, the real-time polarization measurement result shows that the high-risk corroding occurred on the embedded rebar and was validated by directly visualizing the rebar concrete specimen. Therefore, the results obtained allow us to conclude that the disposable of both reference electrodes shows their stability and significantly reduces the reinforced concrete corrosion research cost.